Evaluation of the Corrosion Resistance of AISI 316l Steel Subjected to Severe Deformation Using the Groove Pressing Technique (2019)
In this investigation, samples of AISI 316L steel were subjected to severe plastic deformation by the groove pressing (GP) technique using 2 dies A2 type tool steel dies with dimensions of 96 mm X 96 mm, a corrugated die with 2 mm teeth and 45° angle and a flat die. Each pass through the GP die includes 2 states of corrugated and 2 states of straightening with a 180° rotation between each of them. This configuration provides the material with an equivalent theoretical deformation per pass of ε~1.16. The material was deformed by 4 passes per GP to an equivalent deformation of ε~4.64. Prior to the deformation, the specimens were subjected to an annealing heat treatment for 1 hour at 1000 °C with water cooling, in order to eliminate the lamination texture. The annealed and deformed material was characterized chemically and microstructurally by X-ray fluorescence and scanning electron microscopy, respectively. In order to evaluate the corrosion behavior of the material, linear polarization resistance and analysis by Tafel plot were used in a 0.6 M NaCl solution for 0 and 24 hours. The results show an atypical behavior regarding the corrosion resistance of AISI 316L steel. An increase in corrosion resistance of 45% of the material was observed after 4 passes per GP compared to annealed material (0 passes).